Massive transfusion in upper gastrointestinal bleeding: a new scoring system - Chen, Yi-Chuan; Chuang, Chen-Ju; Hsiao, Kuang-Yu; Lin, Leng-Chieh; Hung, Ming-Szu; Chen, Huan-Wen; Lee, Shung-Chieh (Annals of medicine (Helsinki), 2019)
Background: Massive transfusion in patients with upper gastrointestinal bleeding (UGIB) was not investigated. We developed a new scoring system to predict massive transfusion and to enhance care and early resource mobilization. Methods: Massive transfusion was defined as transfusion with ≥10 units of red blood cells within the first 24 h. Data were extracted from a 10-year, six-hospital database. Logistic regression was applied to derive a risk score for massive transfusion using data from 2006 to 2010, in 24,736 patients (developmental cohort). The score was then validated using data from 2011 to 2015 in 27,449 patients (validation cohort). Area under the receiver operating characteristic (AUROC) curve was performed to assess prediction accuracy. Results: Five characteristics were independently associated (p < .001) with massive transfusion: presence of band-form cells among white blood cells (band form >0), international normalized ratio (INR) >1.5, pulse >100 beats per minute or systolic blood pressure <100 mmHg (shock), haemoglobin <8.0 g/dL and endoscopic therapy. The new scoring system successfully discriminated well between UGIB patients requiring massive transfusion and those who did not in both cohorts (AUROC: 0.831, 95%CI: 0.827-0.836; AUROC: 0.822, 95% CI: 0.817-0.826, respectively). Conclusions: The new scoring system predicts massive transfusion requirement in patients with UGIB well. Key messages Massive transfusion is a life-saving management in massive upper gastrointestinal bleeding. How to identify patients requiring massive transfusion in upper gastrointestinal bleeding is poorly documented. Approximately 3.9% of upper gastrointestinal bleeding patients require massive transfusion. A new scoring system is developed to identify patients requiring massive transfusion with high accuracy.